310 DELETERIOUS ROLE OF CASPASE 3 AND APOPTOSIS IN POLYCYSTIC KIDNEY DISEASE. Issue 1 (1st January 2007) - Tao, Y.; Zafar, I.; Lu, L.; He, Z.; Schrier, R. W.; Edelstein, C. L.
Abstract : Increased apoptosis is a feature of polycystic kidney disease (PKD). Caspases 3 and 7 are the major mediators of apoptosis, and caspase 1 is a proinflammatory caspase. We have previously demonstrated that the pancaspase inhibitor IDN-8050 reduces tubular apoptosis and proliferation and slows disease progression in the Han:SPRD rat model of PKD (Tao, Edelstein, PNAS 2005). However, the exact caspases involved in PKD progression and the effect of specific caspase-3 inhibition on apoptosis in PKD is not known. cpk/cpk mice die of PKD and renal failure between 3 and 4 weeks of age. We backcrossed cpk/ + with caspase 3 +/− mice to develop heterozygous (cpk/cpk casp-3 +/− ) and homozygous (cpk/cpk casp-3 −/− ) double knockout mice. On immunoblot analysis the active form of caspase 3 in the kidney is increased significantly (2.5-fold, p < .05) in cpk/cpk mice compared with +/+ mice, and there was reduced expression of caspase 3 in cpk/cpk casp-3 +/− and no detectable expression in cpk/cpk casp-3 −/− mice. The cpk/cpk casp-3 +/− mice live three times longer (82 vs 24 days, p < .05) and the cpk/cpk casp-3 −/− mice live at least four times longer (117 vs 24 days, p < .001) than cpk/cpk mice. Both cpk/cpk casp-3 +/− and cpk/cpk casp-3 −/− mice have a significantly lower cyst volume density and two kidney/total body weight ratio than cpk/cpk mice. In view of the deficiency of caspase 3, we determined the number of TUNEL-positive apoptotic cells. The number of TUNEL-positive tubular cells/HPF was 0.1 in cpk/cpk, 0.6 in cpk/cpk casp3 +/− mice, and 0.4 in cpk/cpk casp3 −/− mice ( p = NS). Thus, despite the lack of caspase 3, the double-knockout mice still had significant apoptosis. Therefore, we investigated alternative pathways of apoptosis. On immunoblot analysis, caspase 7 was increased 2.6-fold ( p = .03) in cpk/cpk, cpk/cpk casp-3 +/− and cpk/cpk casp-3 −/− versus +/+ littermates. The antiapoptotic protein Bcl-2 decreased significantly (twofold, p = .05) in cpk/cpk, cpk/cpk casp3 +/−, and cpk/cpk casp3 −/− mice compared with wild-type littermates. In summary, our data demonstrate that both heterozygous and homozygous caspase-3 deletion markedly prolongs life in cpk/cpk mice with PKD and that an alternative caspase 7-mediated pathway of apoptosis eventually dominates in the polycystic kidney.